Real Time Tread Width Monitoring Using IoT Sensors: Pemantauan Lebar Tapak Ban Secara Real-Time Menggunakan Sensor IoT - Diva Haristanto; Arief Wisaksono (Indonesian Journal of Innovation Studies, 2025)
General Background: Automated measurement systems are increasingly required in industrial environments to support product quality and operational consistency. Specific Background: In motorcycle tire production, tread width monitoring is commonly performed manually using a roll meter, while tread dimensions vary according to production requirements. This study designed an automatic tread width measurement and monitoring system using VL53L0X sensors, an Arduino Uno microcontroller, an ESP8266 module, an I2C LCD, and Google Sheets for real-time data recording. Knowledge Gap: Previous studies have applied non-contact laser measurement for profile monitoring; however, the integration of automatic tread width measurement with real-time cloud-based monitoring was not addressed. Aims: This study aimed to design and evaluate an automatic system for measuring and monitoring motorcycle tire tread width. Results: The developed system successfully displayed measurement results on an LCD and transmitted data to Google Sheets through serial communication between Arduino Uno and ESP8266. Sensor measurements were generally within acceptable limits, with accuracy ranging from 95% to 100%, while data transmission operated consistently for real-time monitoring. Novelty: The proposed system combines dual VL53L0X-based tread width measurement, local display, and cloud-connected monitoring through Google Sheets within a single integrated platform. Implications: The system provides an alternative to manual measurement methods by offering automated tread width monitoring and online data accessibility for production environments with varying tread sizes.Highlights: Automated dimensional assessment achieved accuracy levels between 95% and 100%. Cloud-connected data transfer operated consistently through ESP8266 communication. Online recording and local display were integrated within one monitoring platform. Keywords: Tread Width Measurement; VL53L0X Sensor; Arduino Uno; Real-Time Monitoring; Google Sheets